STRATEGI PENGEMBANGAN USAHA PRODUKSI PIE SUSU PADA SKALA USAHA RUMAH TANGGA (Studi Kasus Pie Susu Dhian, Denpasar) - Hamonangan Manurung, Binsar; Wrasiati, Ni Luh Putu; Sedana Yoga, I Wayan Gede (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 3 No 1 (2015): Maret)
This study aims to analyze the internal and external conditions and to develop and recommend business development strategies on Pie Susu Dhian Company. This research was conducted in Pie Susu Dhian Company, “Pasar oleh-oleh khas Bali”, Grocery and Supermarkets in the district of Badung and Denpasar. The method used in this study was field observation and in-depth interviews using a questionnaire assistance. Data resulting from field observation and interviews were analyzed to obtain the formulation of strategies using Strengths, Weaknesses, Opportunities, Threaths (SWOT) analysis. Assessment weighting and rating done by 5 experts. The results showed that there were 7 strengths, 4 weaknesses, 5 opportunities, and 3 threats. The results of the weighting and rating assessment were 4,04 for Internal Factor Evaluation (IFE) and 4.22 for External Factor Evaluation (EFE). This value indicates a strong position in the matrix Internal External (IE) with the strategy that should be done were intensive and integrative strategies. Based on the SWOT analysis matrix, there were 10 alternative strategies that will be used to develop business Pie Susu Dhian.
Keywords: 31,